2015
DOI: 10.3390/jmse3041404
|View full text |Cite
|
Sign up to set email alerts
|

Soil Organic Carbon in Mangrove Ecosystems with Different Vegetation and Sedimentological Conditions

Abstract: A large number of studies have been conducted on organic carbon (OC) variation in mangrove ecosystems. However, few have examined its relationship with soil quality and stratigraphic condition. Mangrove OC characteristics would be explicitly understood if those two parameters were taken into account. The aim of this study was to examine mangrove OC characteristics qualitatively and quantitatively after distinguishing mangrove OC from other OC. Geological survey revealed that the underground of a mangrove ecosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 46 publications
(37 reference statements)
0
14
0
6
Order By: Relevance
“…The amount of OC in the sediment is affected by the depth of the soil layer, the type and age of the standing on it [25,26]. The study also showed that OC has a significant association with BD, salinity and pH, similar to the study [27,28]. The distribution of OC in the study site generally shows a decrease in concentration towards the sea [29].…”
Section: Discussionmentioning
confidence: 55%
“…The amount of OC in the sediment is affected by the depth of the soil layer, the type and age of the standing on it [25,26]. The study also showed that OC has a significant association with BD, salinity and pH, similar to the study [27,28]. The distribution of OC in the study site generally shows a decrease in concentration towards the sea [29].…”
Section: Discussionmentioning
confidence: 55%
“…As the TOC % decreased, there was an increase in AMBI values. The high organic matter content may be due to the continuous supply of fresh matter into the system from inland sources as well as the fact that mangrove ecosystems normally act as carbon sinks resulting in higher organic content than would be expected of terrestrial ecosystems (Matsui, Meepol, & Chukwamdee, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Kết quả này phù hợp với nghiên cứu trước đó trong đất RNM [20]. Sơ đồ phân bố các yếu tố gây chua từ đất rừng trong mô hình tôm sinh thái được thể hiện trong Hình 4.…”
Section: Thế Oxy Hóa-khử độ Chua Và Chất Hữu Cơ Trong đấT Rừngunclassified
“…Tương tự như trong đất rừng, sự phân hủy chất hữu cơ giải phóng các acid yếu làm tăng độ chua trong bùn đáy. Kết quả tương tự đã được ghi nhận [20]. Eh biến thiên từ -299 --1 mV (-177,8±14,75 mV).…”
Section: Thành Phần Cơ Giới độ Chua Trao đổI Và Chất Hữu Cơ Trong Bùunclassified